Modulation of Mycobacterium tuberculosis-specific humoral immune responses is associated with Strongyloides stercoralis co-infection. - Rajamanickam Anuradha; Saravanan Munisankar; Yukti Bhootra; Chandrakumar Dolla; Paul Kumaran; Thomas B Nutman; Subash Babu (Public Library of Science (PLoS), 2017)
BACKGROUND / OBJECTIVES:Helminth infections are known to influence T cell responses in latent tuberculosis (LTBI). Whether helminth infections also modulate B cell responses in helminth-tuberculosis co-infection is not known. METHODS:We assessed Mycobacterium tuberculosis (Mtb)-antigen specific IgM and IgG levels, circulating levels of the B cell growth factors, BAFF and APRIL and the absolute numbers of the various B cell subsets in individuals with LTBI, LTBI with coincident Strongyloides stercoralis (Ss) infection (LTBI/Ss) and in those with Ss infection alone (Ss). We also measured the above-mentioned parameters in the LTBI-Ss group after anthelmintic therapy. RESULTS:Our data reveal that LTBI-Ss exhibit significantly diminished levels of Mtb-specific IgM and IgG, BAFF and APRIL levels in comparison to those with LTBI. Similarly, those with LTBI-Ss had significantly diminished numbers of all B cell subsets (naïve, immature, classical memory, activated memory, atypical memory and plasma cells) compared to those with LTBI. There was a positive correlation between Mtb-antigen specific IgM and IgG levels and BAFF and APRIL levels that were in turn related to the numbers of activated memory B cells, atypical memory B cells and plasma cells. Finally, anthelmintic treatment resulted in significantly increased levels of Mtb-antigen specific IgM and IgG levels and the numbers of each of the B cell subsets. CONCLUSIONS:Our data, therefore, reveal that Ss infection is associated with significant modulation of Mtb-specific antibody responses, the levels of B cell growth factors and the numbers of B cells (and their component subsets).